الحروف العاملة وغير العاملة في حاشية العطار (Journal of the College of Basic Education, 2025)
The letter is the source of the meme that is meant by the place of search and research Proof of mobiles for the topics, the meaning is a place where the conditions of the letters are proven to them and carried on themWhich the jurist needs to know its meanings and this is a statement of the excuse of the fundamentalists in their mention of it, although it is from the investigations of grammar, so mentioning it as a matter of principle is not considered a matter of assets or it is said that the research side is heterogeneous, so it is one of its issues. Because of the frequent occurrence in the evidence, but the names will come from them as if the two circumstantials and any aggravating and each in the expression of the predominance of the most, it is not said that the names are more honorable than the letters, so they overcame that it may be said: Do not prevail, the yolk in the explanation of the book (Sibawayh) was quoted as calling the letter the noun and the verb. We have dealt in this research Almstl summary tagged with (working and non-working letters in the footnote of Al-Attar) two sections The first section is the working letters, namely: which affect the names and verbs that enter it syntactically and the second section Non-working letters: which do not affect what follows after the syntactic, but affect the meanings has dealt with a set of letters and tools mentioned by Al-Attar in his footnote, whether they are working, including (Al-Baa, that the source, then) or non-working, including (Hamza, The definition, do) and other letters and God bless.